Performance of Quinoxalinone Derivatives as a Potential Efficient Inhibitor of Ordinary Steel Corrosion in 1 M Hydrochloric Acid: DFT Calculations - Benallal,A. (2023)
Abstract Two quinoxalinone derivatives, namely 3- (p-tolyl)-3.4-dihydroquinoxalin-2-(1H)-one (Q1) and 3-(4-chlorophenyl)-4-methyl-3.4-dihydroquinoxalin-2-(1H)-one (Q2), were used and investigated as potential corrosion inhibitors for OS in a 1 M HCl solution, at C from 10-6 to 10-3 M, using PDP, EIS measurements and GQCD calculations. EIS results indicate that Q1 and Q2 IE(%) increased with higher C and reached maximum values of 86.2 and 92.5%, at 10-3 M, respectively. The inhibitors adsorption mechanism onto the OS surface was found to obey the Langmuir’s adsorption isotherm model. PDP data displayed that Q1 and Q2 acted as mixed inhibitors, predominantly of the cathodic type. The theoretical results showed that the obtained parameters were in good agreement with the experimental data. Q2 compound had better IE(%), due to the inductive effect of CH3 electro-donor group in dihydroquinoxaline position.